ANTERIOR ABDOMINAL WALL HERNIAS AND THEIR SURGICAL TREATMENT IN CIRRHOTIC PATIENTS –LITERATURE REVIEW - E. Merashka (Trakia Journal of Sciences)
The population of patients with chronic liver disease and liver cirrhosis shows increased perioperative morbidity and mortality rates compared to the general population. The severely compromised liver function in combination with the surgical treatment and the specific pathophysiological features of cirrhotic patients contribute to these results.